A political economic analysis of commodified English in South Korean neoliberal labor markets. (November 2018) - Kim, Miso; Choi, Duk-In; Kim, Tae-Young
Abstract: This study examines two contradictions inherent in using English tests for employment by Marx's political economy. English proficiency is quantified by the Test of English for International Communication (TOEIC), mandatory for more than 90% of job posts in Korea. Based on the interviews with jobseekers and human resource managers, the paper reports two contradictions of the TOEIC: first, while the jobseekers perceived the score is inessential, they said the exceptionally high score is required; second, while TOEIC scores are meant to reflect English competence, they do not reflect the competence. These two contradictions emerge because the test is sought for exchange value, rather than use value. The jobseekers invest their resources, produce English scores using labor power and means of production, and finally exchange them for a greater profit. The whole process is geared toward producing scores in the shortest time with maximum efficiency, consequently causing score inflation and separation between genuine English proficiency and test scores. Highlights: There are antagonisms between the use and exchange values of English test scores among South Korean jobseekers. The scores are perceived to have minimal effecton employment, but exceptionally high scores are required. The tests are supposed to measure business-related English competence, but the scores do not reflect the competence. Although the jobseekers seem to be entrepreneurs of human capital, they are estranged from means of production and scores.